The diagnosis of the educational needs of the hearing impaired. (19th January 2010) - Drigas, Athanasios; Kouremenos, Dimitris; Vrettaros, John; Karvounis, Miltos; , Pilios Stavrou
The presented project aims at the examination of the relation of the deaf and hard of hearing people with the new technologies in Greece. The research was conducted through the construction and delivery of an online questionnaire to the members of two deaf organisations in Athens and refers to the motives, for the use of the internet services by deaf people. Particularly, the subject of this project is the comprehension of the needs and wishes of the deaf people regarding the new technologies capabilities as a means of information and communication and whether these capabilities contribute to the active social and economical participation of the people with hearing impairment. Hypotheses and questions are enounced, the survey tool is described as the survey progresses and finally the results of the survey are discussed. This discussion will consist of the basis for the formulation of psychological extensions and technological applications regarding the use of the internet capabilities by people with hearing impairment.